Comparison of Galvanostatic Test Results of Lead Acid and Li-ion Batteries Used in Electric Vehicle Technology - Balci, Esra; Gündüz, Gürkan; Altundağ, Sebahat; Altın, Serdar (Fırat University, 2023)
Ensuring the continuity of renewable energy sources and using electric vehicles instead of internal combustion engines directly affects the environment and quality of life. Studies on batteries that are intended to be developed by adding different metals are still in progress. Batteries with high performance and long service life are demanded in every field today. It also contains important information about the style of writing. In this study, it is aimed to provide general information about Li-ion batteries and lead-acid batteries. The analysis of the electrochemical behavior of the batteries was carried out using the galvanostatic method (100 cycles; under constant current). Fabricated batteries; When the capacity-cycle numbers and charge-discharge curves are examined; It has been shown that the battery (Sony VTC5) in the Li-ion type battery group will offer a longer service life by exhibiting a higher capacity.

Yenilenebilir enerji kaynaklarının sürekliliğini sağlamak ve içten yanmalı motorlar yerine elektrikli araçların kullanılması çevre ve yaşam kalitesini direk etkilemektedir. Farklı metaller katkılanarak geliştirilmesi amaçlanan bataryalar üzerinde çalışmalar hala sürmektedir. Yüksek performans sergileyen ve uzun hizmet ömrü sunabilen bataryalar günümüzde her alanda talep edilmektedir. Bu çalışmada Li-iyon bataryalar ve kurşun-asit aküler hakkında genel bilgilendirme sunulması hedeflenmiştir. Pillerin elektrokimyasal davranışlarının analizi galvanostatik yöntem kullanılarak (100 çevrimde; sabit akım altında) gerçekleştirilmiştir. Hazır üretim olan pillerin; kapasite-döngü sayıları ile şarj-deşarj eğrileri incelendiğinde; Li-iyon türü batarya grubunda yer alan pilin (Sony VTC5) daha yüksek kapasite sergileyerek daha uzun hizmet ömrü sunacağını göstermiştir.
Elektrikli Araç Teknolojisinde Kullanılan Kurşun Asit ve Li-iyon Bataryaların Galvanostatik Test Sonuçlarının Karşılaştırılması
Keywords: Engineering; Mühendislik; Electrical Energy Storage; Elektrik Enerjisi Depolama